SINTESIS SURFAKTAN DIETANOLAMIDA DARI METIL ESTER MINYAK BIJI BUNGA MATAHARI (Helianthus annuus. L) MELALUI REAKSI AMIDASI - Nur Khsanah; Daniel Daniel; Eva Marliana (JURNAL KIMIA MULAWARMAN, 2019)
Synthesis of dietanolamide surfactant from methyl ester of sunflower seed oil (Helianthus annuus. L) has been carried out through an amidation reaction. The synthesis process includes extraction, esterification and amidation. In the extraction process showed the oil content of sunflower seeds was 32.93% with an acid number of 3.25 mg KOH/g and ALB levels of 1.63%. Sunflower seed oil was then converted to methyl ester through the esterification process and obtained an acid number 1.84 mg KOH/g so that the ALB level dropped to 0.92% and obtained saponification numbers of 61.19 mg KOH/g. The most dominant composition of methyl ester of sunflower seed oil based on GC-MS analysis was methyl oleate at 23.28%. The FT-IR methyl ester spectrum gives a specific absorption peak for group C=O ester at wave number 1743 cm-1. Methyl esters are converted to diethanolamide through an amidation process. The resulting diethanolamide has an acid number of 9.7 mg KOH/g and a saponification number of 3.08 mg KOH/g. The FT-IR spectrum provides specific absorption peaks for groups C=O amides at wave numbers 1622 cm-1 and C-N at wave numbers 1055 cm-1. The value of HLB dietanolamide in practice is 13.6495 and in theory is 14.291 which includes the surfactant in the oil in water (O/W) emulsifying class.